2018
DOI: 10.1002/ange.201801592
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐Functional Small Molecules for Generating an Efficient Cytochrome P450BM3 Peroxygenase

Abstract: We report a unique strategy for the development of a H2O2‐dependent cytochrome P450BM3 system, which catalyzes the monooxygenation of non‐native substrates with the assistance of dual‐functional small molecules (DFSMs), such as N‐(ω‐imidazolyl fatty acyl)‐l‐amino acids. The acyl amino acid group of DFSM is responsible for bounding to enzyme as an anchoring group, while the imidazolyl group plays the role of general acid–base catalyst in the activation of H2O2. This system affords the best peroxygenase activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 49 publications
3
30
0
Order By: Relevance
“…Ma et al utilized imidazolyl group based dual-functional small molecules to active H 2 O 2 in the H 2 O 2 -inert P450s catalysis. [40] In our work, we demonstrated the benzene containing small molecules could dock in close proximity to the heme group of OleT (Figure 1B, 1 C, S2), which led to the shifts of heme spectra (Figure 2A, 2B and Figure S3). Our results showed that the enzyme could use H 2 O 2 more efficiently with the presence of such small molecules, likely occurring in the enzyme oxidation step, thus leading to an increased activity.…”
mentioning
confidence: 54%
“…Ma et al utilized imidazolyl group based dual-functional small molecules to active H 2 O 2 in the H 2 O 2 -inert P450s catalysis. [40] In our work, we demonstrated the benzene containing small molecules could dock in close proximity to the heme group of OleT (Figure 1B, 1 C, S2), which led to the shifts of heme spectra (Figure 2A, 2B and Figure S3). Our results showed that the enzyme could use H 2 O 2 more efficiently with the presence of such small molecules, likely occurring in the enzyme oxidation step, thus leading to an increased activity.…”
mentioning
confidence: 54%
“…Based on previous reports, it has become clear that to use the shunt pathway of P450s successfully, two points should be met: 1) A basic group located on the distal side of the heme center is necessary; and 2) The basic group should be placed at a suitable position to ensure that this residue plays the role as an acid-base catalyst efficiently. To this end, Ma et al designed a class of dual-functional small molecules that act as co-catalysts to aid the activation of H2O2 by a modified long-chain fatty acid hydroxylase P450BM3 from Bacillus megaterium (Figure 3) [29][30][31]. Typical structures of DFSMs, such as N-(ωimidazolyl)-fatty acyl-L-amino acid (Im-Cn-AA), are shown in Figure 3B [30].…”
Section: Proof-of-concept Of the Dfsm-facilitated P450 Peroxygenasementioning
confidence: 99%
“…To this end, Ma et al designed a class of dual-functional small molecules that act as co-catalysts to aid the activation of H2O2 by a modified long-chain fatty acid hydroxylase P450BM3 from Bacillus megaterium (Figure 3) [29][30][31]. Typical structures of DFSMs, such as N-(ωimidazolyl)-fatty acyl-L-amino acid (Im-Cn-AA), are shown in Figure 3B [30]. These DFSMs have and acyl amino acid moiety at one end as an anchoring group, i.e., for binding to the enzyme, and an imidazolyl group at the other end as a basic group, which acts as the general acid-base catalyst to activate H2O2 within the heme center.…”
Section: Proof-of-concept Of the Dfsm-facilitated P450 Peroxygenasementioning
confidence: 99%
“…[21] The P450 BM3 F87 A mutant peroxygenase also worked well for the sulfoxidation of thioanisole by using dual-functional small molecules in the presence of H 2 O 2 . [22] To our knowledge, no sulfoxidation of thioanisole has been achieved by using P450 119 peroxygenase.…”
Section: Introductionmentioning
confidence: 99%